A JURISPRUDÊNCIA DOS CONCEITOS E O NEOKANTISMO - André Fontes (TRF2, 2019)
Classification and correlation of German thought forms the mid-nineteenth century to the rise of Nazism is the purpose of this article, with special emphasis on the contribution of Jewish lawyers and their contribution to neokantianism. The text also lists the main theoretical law developments of schools related to the thought of Immanuel Kant.